2005
DOI: 10.4049/jimmunol.174.3.1580
|View full text |Cite
|
Sign up to set email alerts
|

Prototype Alzheimer’s Disease Vaccine Using the Immunodominant B Cell Epitope from β-Amyloid and Promiscuous T Cell Epitope Pan HLA DR-Binding Peptide

Abstract: Immunization of amyloid precursor protein transgenic mice with fibrillar β-amyloid (Aβ) prevents Alzheimer’s disease (AD)-like neuropathology. The first immunotherapy clinical trial used fibrillar Aβ, containing the B and T cell self epitopes of Aβ, as the immunogen formulated with QS21 as the adjuvant in the vaccine. Unfortunately, the clinical trial was halted during the phase II stage when 6% of the participants developed meningoencephalitis. The cause of the meningoencephalitis in the patients that receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
179
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 181 publications
(186 citation statements)
references
References 64 publications
(182 reference statements)
7
179
0
Order By: Relevance
“…37,38,40 In parallel, we conducted therapeutic studies by immunization of 16-19-month-old Tg2576 mice (n = 6). Control animals of the same age were injected with adjuvant alone (n = 5).…”
Section: Experimental Set Imentioning
confidence: 99%
See 1 more Smart Citation
“…37,38,40 In parallel, we conducted therapeutic studies by immunization of 16-19-month-old Tg2576 mice (n = 6). Control animals of the same age were injected with adjuvant alone (n = 5).…”
Section: Experimental Set Imentioning
confidence: 99%
“…30,35,36 In fact, we recently pointed out that active Ab-vaccines tested in clinical trials so far have produced ambivalent results due to their inadequate immunogenicity. 31 To support our position and suggest an effective future clinical trials protocol, we decided for the first time to test the efficacy of our proteinbased epitope vaccine (EV) composed of three copies of immunogenic N-terminal epitope of Ab [37][38][39][40][41] and two Th epitopes from tetanus toxoid (TT) in preventive and therapeutic settings in parallel. More specifically, to simulate disease stages in humans (i.e., prodromal, mild to moderate, and severe AD), we studied the immunogenicity and efficacy of EV (reduction of Ab pathology and cognitive impairments) in Tg2576 mice that, at the start of vaccination, possess low, moderate, and high AD-like pathology.…”
Section: Introductionmentioning
confidence: 99%
“…A prototype epitope AD vaccine was synthesized exactly as we have described previously [36]. Briefly, the N-terminus of the immunodominant B cell epitope of Aβ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] was synthesized in tandem with a promiscuous foreign T cell epitope, PADRE (aK-Cha-VAAWTLKAAa, where "a" is D alanine and "Cha" is L-cyclohexylalanine) as Multiple Antigenic Peptides (MAP), which contain a core matrix of 4 branching lysines [42,43] to generate PADRE-Aβ 1-15 -MAP molecules (Invitrogen Inc., CA).…”
Section: Epitope Vaccine Peptide and Immunizationsmentioning
confidence: 99%
“…To reduce the risk of an adverse T cell-mediated immune response to Aβ-immunotherapy, we developed an epitope vaccine, PADRE-Aβ 1-15 -MAP, and demonstrated that immunizations with this vaccine induced high titers of anti-Aβ antibodies, but not anti-PADRE antibodies. Formulation of our immunogen in the Th2-type adjuvant, Alum, was performed to direct the antibody response toward a Th2 phenotype in an attempt to avoid a strong Th1 humoral response, while maintaining potentially beneficial anti-Aβ antibody response [36]. Alum, however, is much less potent than the majority of Th1-type adjuvants including saponin (QS21) [19,[37][38][39][40], sometimes as much as 200-fold [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation